Contribution to the identification of the professional skills profile of coaches in the algerian sport judo system - Adel, B.; Othman, B.; Mohamed, S.; Abdelhafid, L.; Benkazdali, H. M.; Gleyse, J. (International Journal of Sports Science, 2015)
This study was designed to determine the professional skills of coaches, which are identified and judged based on a large number of factors. The purpose of this article is to describe the views of four groups of professional actors concerning coaches` skills: athletes, coaches, leaders and experts from the Algerian judo sport system. The actors of the system responded to the same series of questions regarding coaches` skills. The actors` views across the five groups of specific professional skills are more similar than dissimilar, with each professional group emphasizing a different item of the coaches` skills. The results show that coaches and athletes have the same representations of technical and teaching skills. However, there is a discrepancy in representations regarding organizational and managerial skills. Stakeholders` views are compared to the coaching science literature, and recommendations for developing a professional skills repository of judo coaches are provided.